Atomic Layer Deposition Alumina‐Mediated Graphene Transfer for Reduced Process Contamination. Issue 11 (29th August 2019) - Shivayogimath, Abhay; Eriksson, Lars; Whelan, Patrick R.; Mackenzie, David M. A.; Luo, Birong; Bøggild, Peter; Booth, Timothy J.
Abstract : Herein, an approach for integrating gate insulator deposition and graphene transfer steps in the fabrication of graphene field‐effect devices is reported. A thin layer of Al2 O3 is deposited by atomic layer deposition (ALD) onto as‐grown graphene on copper, where the improved surface wettability of graphene on copper aids in obtaining a uniform deposition of the ALD layer. The ALD Al2 O3 /graphene stack is then mechanically delaminated from the copper surface and transferred onto the desired target substrate. An ALD layer thickness between 20 and 30 nm is optimal for facilitating such transfer. The ALD layer protects graphene from process contamination during subsequent transfer and device fabrication, resulting in reduced doping in measured field‐effect devices. Abstract : An approach for integrating gate insulator deposition and graphene transfer steps in the fabrication of graphene field‐effect devices by encapsulating as‐grown graphene on the metal catalyst prior to transfer onto a target substrate is presented. This protects the graphene from process contamination during subsequent transfer and device fabrication, resulting in reduced doping in measured field‐effect devices.